Factors Affecting the Slenderness Limit for RC Columns-The Use of the (ACI-318M-05) Provisions - Al-Sharrbaf, Ihsan A. S.; Al-Bakri, Bassman R.; . Al-Nu man, Bayan S; Sarsam, Kaiss F. (Nahrain University College of Engineering Journal, 2008)
The current ACI code and many other codes permit the moment magnification method for design of slender reinforced concrete (RC) columns. Manually, the design/analysis procedure is tedious, so that the codes state a pre-prediction if the column is slender or not. In other words, before starting design codes provide slenderness limits to be considered to decide whether a column is slender or not. This work will concentrate on the slender RC column provisions of the latest ACI Code. Using this method some columns are found to be short. In the proposed method of this work, it is found that some of these short columns are found to be long , thus needing moment magnification. Since column analysis/design represents dealing with one of the most critical parts of RC buildings, this proposed magnification is presented in this work.